KAJIAN RANTAI PASOK BERAS DI DISTRIK TANAH MIRING KABUPATEN MERAUKE - Marthen A. I. Nahumury; Maria M. D. Widiastuti (AGRICOLA, 2015)
This study aims to assess the rice supply chain and analyze the efficiency of rice supply chain in Tanah Miring District. The methodology used a snowball sampling. The sample of respondent consist of 50 farmers in 5 villages, 20 supplier (Rice Milling Unit), 10 trader in medium scale and 10 trader in big scale at Merauke District. The results showed that rice supply chain in Tanah Miring District have a six-channel. Channel one: farmers-end consumers, channel two: farmers-big trader-medium trader-retailer-end consumers, channel three: farmers-big trader-medium trader-end consumers, channel four: farmers-medium trader-retailer-end consumers, channel five: farmers-retailers-end consumers and channel six: farmers-big trader-district logistic agency (Bulog)-end consumers.The efficient channel was channel one, was sell directly to the end consumer.